ANALISIS PENGARUH EARNING PER SHARE, DIVIDEND PER SHARE, DAN FINANCIAL LEVERAGE TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2016 - Baiq Reinelda Tri Yunarni Tri Yunarni; Muhammad Yusril; Selva Selva (Jurnal Ilmiah Mandala Education (JIME), 2017)
The purpose of this study is to investigate the influence of earnings per share (EPS), dividend per share (DPS), and financial leverage (FL) empirically on the stock price. This research is a kind of causal research and be replicated on a previous study with the study population are manufacturing companies listed in Indonesia Stock Exchange (IDX) during the period 2013-2016. The data used are secondary data. This study analyzes the relationship among earnings per share (EPS), dividend per share (DPS), and financial leverage (FL) to the stock price. The method used is multiple linear regression to test the classical assumption first. The results of this study indicate that partial three variables have different results in which earnings per share (EPS) positive effect on stock prices of manufacturing companies listed on the BEI period 2013-2016, while the dividend per share (DPS) and financial leverage (FL ) does not affect the stock price manufacturing companies listed on the Stock Exchange and simultaneously 2013-2016 period, earnings per share (EPS), dividend per share (DPS), and financial leverage (FL) did not affect stock prices in manufacturing companies listed in BEI 2013-2016